Analisis Prospektif Peremajaan Kelapa Sawit (Elaeis Guineensis Jacq) POLA Swadaya di Kabupaten Kampar - Kartika Malau; Novia Dewi; Syaiful Hadi (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2023)
This study aims to analyze oil palm farming self-help patterns and determine the determinants of successful replanting and the implications of self-help oil palm replanting. The analysis used is a prospective analysis. The results of this study show that independent oil palm farmers in Kampar Regency have an average net income obtained by farmers of 38,814,983.21 / lg / th and the determining attributes for the success of oil palm replanting in Kampar Regency are banks, assistance workers and partners. These attributes have a strong influence on the success of oil palm replanting and there are implications for the development of oil palm replanting self-help patterns in this study, namely improvements in the components of the attributes of ease of selling production products, high demand, knowledge and skills of farming, controlled prices, capital and land legality.